The making and unmaking of Francoist kitsch cinema : from Raza to Pan's Labyrinth - Yarza, Alejandro, 1958- (Edinburgh University Press, 2018)
This book examines five highly influential Francoist films produced from 1938 until 1964 and three later films by critically acclaimed directors Luis BuÃ³Âłuel, Guillermo del Toro, and Alex de la Iglesia that attempt to undermine Francoist aesthetics by re-imagining its visual and narrative cliches.